ANALYSIS OF GOODS MANAGEMENT SYSTEM IN THE COMMUNICATION AND INFORMATICS DEPARTMENT OF SERDANG BEDAGAI DISTRICT - Cut Try Utari; Richard Parlindungan Simanjuntak; Firman Styono; Junerdi Nababan (Jurnal Techno Nusa Mandiri, 2023)
The current problem is that the Serdang Bedagai district communication and informatics office is experiencing difficulties in managing incoming and outgoing goods. Management is currently carried out manually and cannot be viewed online so that many errors occur, one of which is a mismatch between the stock of goods recorded and the physical stock of existing goods. The goods management system that will be built in this study uses the waterfall model and PHP and HTML programming languages as well as CSS to design the web appearance. The system has 9 entities, namely: officer, user, sender, person in charge, goods, recipient, detail_recipient, expenditure and data_dinas. The results of the implementation of the proposed system are more optimal management of goods and help the performance of the warehouse admin in making real-time stock update reports and borrowing goods